ANALYSIS OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE UPTD OF SUNGAI IYU COMMUNITY HEALTH CENTER, ACEH TAMIANG DISTRICT - Nursyah Dila; Marbawi; Em Yusuf Is; Yusniar (RADJA PUBLIKA, 2025)
The purpose of this study is to determine the analysis of work motivation on employee performance with job satisfaction as an intervening variable at the UPTD Puskesmas Sungai Iyu in Aceh Taming District. This study uses a quantitative approach with a survey method. The population in this study consists of 82 employees, with a sample size of 68 respondents determined using the Slovin formula. Data collection was conducted through a closed-ended questionnaire using a Likert scale, which was then analyzed using multiple linear regression with SPSS 26 software and the Sobel test to examine the mediating effect. The results of the study indicate that work motivation has a positive effect on employee performance. Work motivation has a positive effect on job satisfaction. Job satisfaction has a positive effect on job satisfaction. Additionally, work motivation has an indirect effect on employee performance through job satisfaction as an intervening variable, with a significant Sobel test.